2010
DOI: 10.1016/j.bpj.2009.12.2321
|View full text |Cite
|
Sign up to set email alerts
|

The Two Enantiomers of Citalopram Bind to the Human Serotonin Transporter in Reversed Orientations

Abstract: Biological function of proteins is frequently associated with the formation of complexes with small-molecule ligands. Experimental structure determination of such complexes at atomic resolution, however, can be time-consuming and costly. Computational methods for structure prediction of protein/ligand complexes, particularly docking, are as yet restricted by their limited consideration of receptor flexibility, rendering them not applicable for predicting protein/ligand complexes if large conformational changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 0 publications
5
33
1
Order By: Relevance
“…It has been demonstrated that S-citalopram has a competitive mode of inhibition in SERT (22,23), which is consistent with overlapping binding sites for 5-HT and Scitalopram (13,16). To elucidate the mode of inhibition by Rtalopram, we performed uptake-saturation experiments with SERT and NET in the absence or presence of inhibitors (SI Experimental Procedures), which revealed a competitive mode of inhibition for S-citalopram and R-talopram in both SERT and NET (Table S3).…”
Section: Structural Features Of Inhibitors Underlying Activity and Sesupporting
confidence: 55%
See 3 more Smart Citations
“…It has been demonstrated that S-citalopram has a competitive mode of inhibition in SERT (22,23), which is consistent with overlapping binding sites for 5-HT and Scitalopram (13,16). To elucidate the mode of inhibition by Rtalopram, we performed uptake-saturation experiments with SERT and NET in the absence or presence of inhibitors (SI Experimental Procedures), which revealed a competitive mode of inhibition for S-citalopram and R-talopram in both SERT and NET (Table S3).…”
Section: Structural Features Of Inhibitors Underlying Activity and Sesupporting
confidence: 55%
“…Citalopram and talopram are racemic mixtures, and it is wellestablished that the inhibitory potency of citalopram toward SERT resides in the S-enantiomer (16,20,21), as exemplified by Lexapro. Accordingly, we found that the affinity of S-citalopram was 35-fold higher for SERT compared with R-citalopram (4 nM versus 136 nM), whereas both enantiomers displayed low affinity binding to NET (3,025 nM versus 1,516 nM) ( Fig.…”
Section: Structural Features Of Inhibitors Underlying Activity and Sementioning
confidence: 99%
See 2 more Smart Citations
“…3A), while the tricyclic antidepressant imipramine is also thought to interact strongly with the Asp98 residue 13,32,37 . A study by Koldsø et al (2010) discovered that the two enantiomers of the SSRI citalopram bind to a central binding site of the hSERT homology model with reversed orientations 38 . It has also been previously shown that the protonated amine of a series of sulfur-substituted -alkyl phenethylamines is essential for protein-ligand binding.…”
Section: Molecular Modellingmentioning
confidence: 99%